MINAT SISWA TERHADAP PEMBELAJARAN SENI MUSIK DI SMP NEGERI 1 PAINAN KABUPATEN PESISIR SELATAN - Suyata Suyata; Tulus Handra Kadir; Marzam Marzam (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of this study was to reveal the picture of students' interest to wards learning the art of music in SMP Negeri 1 Painan South Coastal District. This type of researc his descriptive, while research conducted in February-March 2013. The instrument used was a questionnaire to collect data using a Likert scale. Data were analyzed using frequency distribution formula in the form of a percentage. From the analysis of the data obtained the following results: 1. Minat siswa in SMPN egeri 1 Painan seen from the classification indicators are sufficient participation (74.1%). 2. Student interest in SMP Negeri 1 Painan seen from the classification indicators are sufficient attention to the percentage of75.7%. 3. Student interest in SMP Negeri 1 Painan seen from the feeling of being on the classification of the indicators enough with the percentage of 79.3%. It means that of the three indicators of interest needs to be improved, so that students become better. Kata kunci : Minat, pembelajaran, musik, deskriptif.